2014
DOI: 10.1177/0300060513509036
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane/remifentanil versus propofol/remifentanil for electroconvulsive therapy: Comparison of seizure duration and haemodynamic responses

Abstract: Objective: To compare the anaesthetic and convulsive effects of sevoflurane/remifentanil versus propofol/remifentanil combination in electroconvulsive therapy (ECT). Methods: In this prospective, randomized double-blind study, patients diagnosed with treatmentresistant depression were included for ECT. Prior to treatment, 1 mg/kg remifentanil was intravenously administered to all patients, followed by anaesthetic induction with either 0.5 mg/kg propofol or 8% sevoflurane. Following muscular paralysis with succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…When compared with ketamine, thiopental, methohexital and etomidate in both randomised blinded and retrospective studies, propofol is associated with shorter seizure durations (8,21,27,28), more missed seizures and significantly more electrical current is required to treat (29,30). In prospective randomised studies propofol provides a better recovery and haemodynamic profile than the other agents (21,31,32). In regards to the clinical effect of ECT, propofol has been shown to be associated with better or faster outcome than thiopental in prospective randomised studies (8,33).…”
Section: Resultsmentioning
confidence: 99%
“…When compared with ketamine, thiopental, methohexital and etomidate in both randomised blinded and retrospective studies, propofol is associated with shorter seizure durations (8,21,27,28), more missed seizures and significantly more electrical current is required to treat (29,30). In prospective randomised studies propofol provides a better recovery and haemodynamic profile than the other agents (21,31,32). In regards to the clinical effect of ECT, propofol has been shown to be associated with better or faster outcome than thiopental in prospective randomised studies (8,33).…”
Section: Resultsmentioning
confidence: 99%
“…64 Studies comparing propofol versus sevoflurane with respect to seizure duration have reported mixed results. 65,66 The anesthetic doses are usually kept to minimum during ECT in view of their anticonvulsant attribute and to allow early recovery. Nonetheless, without further reducing the dose of the anesthetic, if the peak anesthetic action is allowed to wear off before giving ECT stimulation, seizure prolongation can be achieved.…”
Section: Endocrine Diseasesmentioning
confidence: 99%
“…Der exakte Einfluss der "Qualität" und Länge des Krampfanfalls auf das Behandlungsergebnis ist nicht abschließend geklärt [91][92][93]. Remifentanil zeigte in mehreren Untersuchungen eine bessere hämodynamische Stabilität sowie längere und "qualitativ bessere" Krampfanfälle [94][95][96]. Eine Metaanalyse aus dem Jahr 2014 und eine Übersichtsarbeit aus dem Jahr 2016 ermittelten hinsichtlich des psychiatrischen Ergebnisses keine Überlegenheit eines anästhesiologischen Verfahrens gegenüber einem anderen, schloss Remifentanil aber nicht ein [97,98].…”
Section: Analgosedierung Zur Elektrokrampftherapieunclassified